(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The City of Candon in Ilocos Sur, Philippines, is rich in culturally built heritage, particularly houses of ancestry. The City identifies ancestral houses, while other buildings and structures are not included in the list but can already be considered part of the culturally built heritage. Collectively, these cultural resources are within a proposed heritage district of the City, including a heritage growth corridor–where the high concentration of such resources is located – that may serve as a visual representation and act as a living museum of the area. This study formulated a proposed Heritage Resources Conservation Plan to preserve and protect the identified built heritage resources in Candon City. A field survey was conducted to identify and map the local heritage resources and their cultural significance. Upon identification of the City’s heritage district, several guidelines regarding further development in the area, especially along the heritage corridor, were recommended to preserve and protect these cultural resources from possible deterioration and destruction.